Transgression of Desire in Erotica Based on the Psychoanalysis of Jacque Lacan and George Bataille - Tuwio, Namuri Migo; Djohan, Djohan; Harsanto, Prayanto Widyo (Graduate School of Institut Seni Indonesia Yogyakarta, 2024)
This study aims to develop a new discourse of eroticism based on the experience of sexual fantasy as an effort to find